Similar virus spectra and seasonality in paediatric patients with acute respiratory disease, Ghana and Germany. (April 2016) - Annan, A.; Ebach, F.; Corman, V.M.; Krumkamp, R.; Adu-Sarkodie, Y.; Eis-Hübinger, A.M.; Kruppa, T.; Simon, A.; May, J.; Evans, J.; Panning, M.; Drosten, C.; et al.
Abstract: Epidemiological differences between tropical and temperate regions regarding viruses causing acute respiratory infection are poorly understood. This is in part because methodological differences limit the comparability of data from these two regions. Using identical molecular detection methods, we tested 1174 Ghanaian and 539 German children with acute respiratory infections sampled over 12 months for the 15 most common respiratory viruses by PCR. A total 43.2% of the Ghanaian and 56.6% of the German children tested positive for at least one respiratory virus. The pneumoviruses respiratory syncytial virus and human metapneumovirus were most frequently detected, in 13.1% and 25.1% within the Ghanaian and German children, respectively. At both study sites, pneumoviruses were more often observed at younger ages (p <0.001). In the Ghanaian rainy season, enveloped viruses were detected twice as often as non-enveloped viruses (prevalence rate ratio (PR) 2.0, 95% CI 1.7–2.4). In contrast, non-enveloped viruses were more frequent during the Ghanaian dry season (PR 0.6, 95% CI 0.4–0.8). In Germany, enveloped viruses were also more frequently detected during the relatively colder winter season (PR 1.6, 95% CI 1.2–2.1) and non-enveloped viruses during summer (PR 0.7, 95% CI 0.5–0.9). Despite a distance of about 5000 km and a difference of 44° latitude separating Germany and Ghana, virus spectra, age associations and seasonal fluctuation showed similarities between sites. Neither respiratory viruses overall, nor environmentally stable (non-enveloped) viruses in particular were more frequent in tropical Ghana. The standardization of our sampling and laboratory testing revealed similarities in acute respiratory infection virus patterns in tropical and temperate climates.